Usage of electronic resources among the community of the faculty of computer science and information technology, Universiti Putra Malaysia - Abdullah, Salmah; Iberahim, Zubaidah; Engku Mud, Tengku Nor Fazwani; Khahirullah, Khairil Ridzuan; Ab Llah, Liza; Hamdan, Noorhaniza; Zainal Abidin, Azizah (Persatuan Pustakawan Malaysia, 2018)
The purpose of this study was to examine the utilization of electronic information resources (e-resources) by the community of the Faculty of Computer Science and Information Technology (FSKTM), Universiti Putra Malaysia (UPM).A specifically designed sets of questionnaire were distributed to gather information on the frequency of e-resource usage and the perceptions of users towards the subscribed e-resources namely IEEE, Pro Quest Central, Science Direct, Springerlink and Wiley. The questionnaires were distributed within the FSKTM community in October 2018. A total of 350 questionnaires were distributed and 178 were returned with a 50.8% response rate. Data were analyzed using SPSs.The study concluded that Perpustakaan Sultan Abdul Samad (PSAS) should monitor and promote the use of e-resources subscribed by the Library and continue their subscription. The average use of IEEE, Science Direct and Wiley were found to be weekly and the Springerlink databases was used daily. Thus,active and urgent actions are needed to increase the use of these e-resources.The study also found that the main problem encountered when using the eresources were slow internet connection, network downtime and off-campus access/ez-proxy problems. Meanwhile, the main problem associated with the non-use of e-resources ,\'as lack of adequate information searching skills that was mainly due to the absence of e-resources skills courses.